Anti-Type VII Collagen Antibodies Are Identified in a Subpopulation of Bullous Pemphigoid Patients With Relapse - Giusti, Delphine; Gatouillat, Grégory; Le Jan, Sébastien; Plée, Julie; Bernard, Philippe; Antonicelli, Frank; Pham, Bach-Nga (Frontiers in Immunology, 2018)
Bullous pemphigoid (BP) is an autoimmune bullous skin disease characterized by anti-BP180 and anti-BP230 autoantibodies. Mucous membrane involvement is an uncommon clinical feature of BP which may evoke epidermolysis bullosa acquisita (EBA), another skin autoimmune disease characterized by anti-type VII collagen autoantibodies. We therefore evaluated the presence of anti-type VII collagen autoantibodies in the serum of BP patients with and without mucosal lesions at time of diagnosis and under therapy. Anti-BP180, anti-BP230 and anti–type VII collagen autoantibodies were measured by ELISA in the serum of unselected patients fulfilling clinical and histo/immunopathological BP criteria at baseline (n=71) and at time of relapse (n=24). At baseline, anti-type VII collagen autoantibodies were detected in 2 out of 24 patients with BP presenting with mucosal involvement , but not in patients without mucosal lesions (n=47). At the time of relapse, 10 out of 24 BP patients either displayed a significant induction or increase of concentrations of anti-type VII collagen autoantibodies (P <0.01), independently of mucosal involvement. Those 10 relapsing BP patients were also characterized by a sustained high concentration of anti-BP180 autoantibody, whereas the serum anti-BP230 autoantibody concentrations did not vary in BP patients with relapse according to the presence of anti-type VII collagen autoantibodies. Thus, our study showed that anti-type VII collagen along with anti-BP180 autoantibodies detection stratified BP patients at time of relapse, illustrating a still dysregulated immune response that could reflect a potential epitope spreading mechanism in those BP patients.